Management of premature end-of-life vehicles in developing countries: Lessons from Nairobi City County, Kenya - Selelah Okoth; Elvin Nyukuri; Richard Mulwa (Center for Science and Technology, IAIN Surakarta, 2023)
Premature end-of-life Vehicles (ELVs) are on the rise in Kenya due to an increase in road accidents, as reported by National Transport and Safety Authority. These premature ELVs are poorly managed, frequently found parked in police station yards, garages, and residential estates, posing risks to public health and environment, thus undermining progress toward sustainable development goals. There have been scattered efforts on their management through policies and legislation, such as the Environmental Management and Coordination Act of 1999; the umbrella law on environment,which remains generic and insufficient in effectively addressing premature ELVs. This article presents the findings of a study conducted to assess the existing management mechanisms of premature ELVs in Nairobi City County. The study employed semi-structured questionnaires administered to households (n = 170) and conducted key informant interviews (n = 88) within relevant agencies in the County. The results show that the most common mechanism for handling premature ELVs is their sale to garages for spare parts sourcing (31%), while the least utilized method invloves selling them for recycling (3%). Furthermore, there exists an opportunity to implement circular economy principles in the management of premature ELVs. Consequently, there is a pressing need for government to develop appropriate policies, legal frameworks, and institutional support to effectively manage premature ELVs.